Clay and organic matter applications on the coarse quartzy tailing material and the sorghum growth on the post tin mining at Bangka Island - M Nurcholis; A Wijayani; A Widodo (Journal of Degraded and Mining Lands Management, 2013)
Artisanal mining on the island ofBangkaleaves a lot of damaged landsurfacecoveredbycoarse-sized tailings that are dominatedby thequartz mineral and it causes soil to be extremely unfertile. The objective of the present research wastounderstand the impact of the clay and organic matter(OM) applications on the tailingsforsupportingthe growth of anadaptiveplant whichis usedinthe present studyissorghum. Thestudywas conducted on the artisanal mine closure land at Pangkalpinang, theclaymaterial andcow dung were collected fromlocally near location. Land was preparedby constructingfour treatments, i.e.: control, OM + NPK, clay + OM,andclay + OM + NPK. The amendment materialswereapplied by mixing the tailing on the 30 cm wide and depth on eachplantingstripwith a distance of70 cm. Sorghumseedswere plantedwith a spacingof 20 cm. Wateringplants was done byutilizingthe waterpitat the beginning ofgerminationand plant growth. The results showed thatsorghumgrownandsurvivedonlyonemonthinthe control treatment. Sorghumgrowthis verygoodon the treatment ofclay+OM+NPK, while the othertwo treatmentsresult instuntedgrowth ofsorghum. <w:LsdException Locked="false" Priority="65" SemiHidden="false" UnhideWhenUsed="false" Name="Medium List 1 Accent 3"